Comparison of culture and different PCR assays for detection of Trichomonas vaginalis in self collected vaginal swab specimens. Issue 5 (22nd October 2003) - Crucitti, T; Van Dyck, E; Tehe, A; Abdellati, S; Vuylsteke, B; Buve, A; Laga, M
Abstract : Objectives: DNA amplification techniques have become widely used for the diagnosis of sexually transmitted infections. For the detection of Trichomonas vaginalis, PCR techniques are not yet widely used despite the publication of several assays. The sensitivity and specificity of five independent primer sets were determined on self collected vaginal specimens obtained from female commercial sex workers. Methods: Self collected specimens were obtained from symptomatic and asymptomatic women attending a female sex workers clinic in Abidjan, Côte d'Ivoire. Two vaginal specimens were collected, the first one was processed for culture and the second was processed for PCR analysis. PCR techniques for trichomonads were performed, using the primers as reported by Riley (TVA5/TVA6), Kengne (TVK3/TVK7), Madico (BTUB 9/BTUB 2), Shiao (IP1/IP2), and Mayta (TV1/TV2). An EIA amplicon detection method was designed for each of the primer sets. Results: True positive specimens were defined as culture positive and/or two positive PCR results with EIA amplicon detection in any combination. According to this definition a prevalence of 20% was obtained compared to 7% obtained by culture. The PCR primer set TVK3/TVK7 gave the highest sensitivity (89.2%). Poor sensitivities were obtained with the primer sets TV1/TV2 (60.2%) and TVA5/TVA6 (63.9%). PCR showed a sensitivity improvement of 2.4% up to 12% when EIA was used for amplicon detection. Conclusions: Overall, the sensitivities of the different PCR assays resulting from this study were lower than those previously described. These findings could be the result of the nature of the specimen population and suggests a strain variability.